2006
DOI: 10.1079/pgr2006123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Helicoverpa and drought resistance in desi and kabuli chickpea

Abstract: A chickpea collection of 1600 desi and 1400 kabuli were evaluated for yield losses arising from pod borer (Helicoverpa armigera) infestation under rainfed conditions by spraying half the plots to prevent pod borer infestation and allowing the other half to be infested. From these lines, 82 were selected for further detailed evaluation of Helicoverpa resistance and drought resistance under irrigated and rainfed conditions. The yield losses from Helicoverpa damage varied from 10 to 33% depending on the chickpea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 7 publications
1
43
0
Order By: Relevance
“…Chickpea is well known to be susceptible to flooding and excess moisture (Yadav et al, 2006). Under high moisture condition chickpea is prone to fungus and wilt diseases (Yadav et al, 2006). During the present investigations, we did not find autoclaved soil mixture in any way to be an essential requirement for the establishment of in vitro raised plantlets of chickpea.…”
Section: Successful Establishment Of In Vitro Raised Plantletsmentioning
confidence: 52%
See 2 more Smart Citations
“…Chickpea is well known to be susceptible to flooding and excess moisture (Yadav et al, 2006). Under high moisture condition chickpea is prone to fungus and wilt diseases (Yadav et al, 2006). During the present investigations, we did not find autoclaved soil mixture in any way to be an essential requirement for the establishment of in vitro raised plantlets of chickpea.…”
Section: Successful Establishment Of In Vitro Raised Plantletsmentioning
confidence: 52%
“…of India) in the ratio of 1:1:1 ( Figure 3B) is most suitable for achieving cent percent transplantation success. Chickpea is well known to be susceptible to flooding and excess moisture (Yadav et al, 2006). Under high moisture condition chickpea is prone to fungus and wilt diseases (Yadav et al, 2006).…”
Section: Successful Establishment Of In Vitro Raised Plantletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yadav et al (2006) also reported resistant genotypes of chickpea both against H. armigera and drought. Similarly, significant interaction was found between drought and genotypes of soybean for herbivores (Helicoverpa zea and Spodoptera exigua) (Grinnan et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Chickpea is well known for its vulnerability to flooding and excess moisture. Also under high moisture conditions, chickpea is prone to fungus and wilt diseases (Yadav et al, 2006). Ascochyta blight disease is a major disease seen in chickpea, affecting the yield about 50-80%.…”
Section: Introductionmentioning
confidence: 99%